Estimation of global solar radiation on inclined surfaces - Maleki, Seyed Abbas Mousavi (2016)
Generally, in the weather stations, the global solar radiation is measured on horizontal surfaces. However, to maximize the amount of solar radiation incident on the collector surface, stationary solar convention systems, both solar photovoltaic and flat plat solar collectors, are mounted on inclined surfaces. It is not an easy task to measure global solar radiation on inclined surface, mainly due to the high price of measuring equipment and technique needed to do so.Hourly global solar radiation on inclined surfaces can be estimated from global solar radiation on horizontal surfaces by several models. These models can be used to estimate components of hourly global solar radiation on horizontal (direct and diffuse radiation) and inclined surfaces (direct, diffuse and ground reflected radiation).The main objective of this research was to recognize the most accurate model of estimating global solar radiation on inclined surfaces for Malaysia. In this research the hourly global solar radiation on horizontal surfaces was taken from a meteorological weather station in Universiti Putra Malaysia (UPM) for a year. To achieve this objective, the hourly global solar radiation on inclined surfaces was estimated by 126 combined models at three different angels. Moreover, hourly global solar radiation on inclined surfaces was measured at the same angles for a time from August 2014 to October 2015. The comparison between the estimated values and measured values was made based on three statistical methods. The values of monthly optimum tilt angle based on two accurate models were identifed and compared with that of the yearly tilt angle for a period of around 89 days, as recommended by previous researchers.